Impact of cancer service centralisation on the radical treatment of men with high‐risk and locally advanced prostate cancer: A national cross‐sectional analysis in England. Issue 1 (17th January 2019) - Parry, Matthew G; Sujenthiran, Arunan; Cowling, Thomas E; Nossiter, Julie; Cathcart, Paul; Clarke, Noel W; Payne, Heather; Aggarwal, Ajay; van der Meulen, Jan
Abstract : In many countries, specialist cancer services are centralised to improve outcomes. We explored how centralisation affects the radical treatment of high‐risk and locally advanced prostate cancer in the English NHS. 79, 085 patients diagnosed with high‐risk and locally advanced prostate cancer in England (April 2014 to March 2016) were identified in the National Prostate Cancer Audit database. Poisson models were used to estimate risk ratios (RR) for undergoing radical treatment by whether men were diagnosed at a regional co‐ordinating centre ('hub'), for having surgery by the presence of surgical services on‐site, and for receiving high dose‐rate brachytherapy (HDR‐BT) in addition to external beam radiotherapy by its regional availability. Men were equally likely to receive radical treatment, irrespective of whether they were diagnosed in a hub (RR 0.99, 95% CI 0.91–1.08). Men were more likely to have surgery if they were diagnosed at a hospital with surgical services on site (RR 1.24, 1.10–1.40), and more likely to receive additional HDR‐BT if they were diagnosed at a hospital with direct regional access to this service (RR 6.16, 2.94–12.92). Centralisation of specialist cancer services does not affect whether men receive radical treatment, but it does affect treatment modality. Centralisation may have a negative impact on access to specific treatment modalities. Abstract : What's new? More than one‐quarter of men with high‐risk or locally advanced prostate cancer in England do not receive radical treatment with radiotherapy or surgery, potentially owing to differences in treatment access. Here, prostate cancer service centralisation in England was investigated for potential impacts on treatment access. Among English patients in the National Prostate Cancer Audit database, centralisation had no impact on decisions to use radical treatment. It did, however, affect treatment option availability, with potential consequences for patient outcome. Patients were more likely to undergo surgery or high dose‐rate brachytherapy when diagnosed at hospitals with direct links to these services.